ANALISIS KAPASITAS JALUR DAN KECELAKAAN KERETA API - Malkamah, Siti; Muthohar, Imam; Murwono, Djoko; Wiarco, Yuwono (FSTPT Indonesia, 2015)
Train is an efficient public transportation that need to be developed. Currently, the development of railway infrastructures is already showing some improvements. One of them is the completion of Jakarta-Surabaya double track. With the construction of the double track, the railway capacity increased. However, research on the railway capacity in Indonesia is still limited. There was still inefficiency in using the railway capacity by the operator. This research aims to investigate the factors that affect the capacity and the relationship between railway capacities and train accidents. The data required were obtained from PT Kereta Api (Persero) and the Ministry of Transportation and from site visits. The data were then abstracted and analysed. It was found that there was a decrease in the number of accidents in 2010 - 2014, with a variety of causes such as: infrastructure, facilities, human and external factors. The construction of a doubl-track railway had contributed to the decline of the accidents. This is due to the construction of a double track increased the railway capacity. It resulted in the loss of intersection or crossing points. Those crossing points were the critical points of the accidents. The declining of forwarding of train travel increased speed and travel time. The increase of capacity and safety finally improved the train services for both passengers and goods.